Synthesis, electrochemical and spectroelectrochemical properties of novel soluble peripheral tetra triazole substituted Co-II, Cu-II, (MnCl)-Cl-III and (TiO)-O-IV phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This paper reports the synthesis, electrochemical and spectroelectrochemical properties of peripherally tetra-substituted metallophthalocyanines (M = Co-II, Cu-II, (MnCl)-Cl-III and (TiO)-O-IV) which contain 4-(3,4-dimethoxyphenethyl)-5-ethyl-2H-1,2,4-triazol-3(4H)-one. The precursor phthalonitrile compound (3) for the phthalocyanine formation was synthesized in the first step. Subsequently, related metallophthalocyanine complexes of cobalt(II) (3-Co), copper(II) (3-Cu), manganese(III) (3-Mn) and oxo-titanium(IV) (3-Ti) were synthesized. The characterization of all these compounds was accomplished using prevalent spectroscopic techniques. Electrochemical characterization of the metallophthalocyanines (MPcs) bearing redox active Co2+ and Mn3+ metal centers, in addition to the redox inactive Cu2+ ion, were performed to investigate the effects of electron transfer reactions from the metal center on the redox features of the Pc ring. While the CuPc (3-Cu) illustrated three Pc based reduction reactions and one Pc based oxidation reaction, incorporation of redox active Co2+ and Mn3+ metal centers instead of Cu2+ increased the redox richness of the complexes, with additional metal based reduction and oxidation reactions. While the CoPc (3-Co) gave one metal-based reduction and one metal based oxidation reaction, in addition to the redox processes of Pc ring, the MnClPc (3-Mn) gave to two metal-based reduction reactions. All the redox processes had almost chemically and electrochemically reversible character, except those observed at the solvent windows. An in situ spectroelectrochemistry technique was used for the assignment of the redox couples and to determine the optical responses of the electrogenerated species. (C) 2020 Published by Elsevier Ltd.
Keywords: Synthesis; Triazole; Phthalocyanines; Electrochemistry; Spectroelectrochemistry; METAL-FREE; COBALT; MANGANESE; METALLOPHTHALOCYANINES; ELECTROPOLYMERIZATION; BEHAVIOR; NICKEL; CO(II); COPPER; IRON